Humanities dissertation abstracts in Indonesian and English universities: a comparative move analysis - Eri Kurniawan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Recent years have seen a surge in exploring rhetorical moves and linguistic features in a wide range of academic texts. However, little attention has been paid to a comparative analysis of doctoral theses from different countries. This study aims to uncover the rhetorical organization and linguistic characteristics of dissertation abstracts from higher education institutions in two different cultural backgrounds. Dissertation abstracts in the fields of humanities, including linguistics, literature, and law, were examined from a total of four top-ranked universities in England and Indonesia, using Hyland’s (2000) model as the analytical framework. In terms of rhetorical organization, the findings revealed that the Introduction – Purpose – Method – Product move pattern was the most common in the abstracts of both groups of corpus data. A notable difference was found in the writing of the Product (Move 4), which was used exclusively in the English data group to outline research findings per chapter. As for linguistic features, the Indonesian data differed from the English counterparts mainly in their use of Relational Verbs, while both data sets were similar in their use of verb tenses, voice, and modality preferences. In conclusion, regardless of distinct cultural and academic settings, no substantial differences were found between the dissertation abstracts of the four universities under investigation. Further comparative research on this topic with different data sets and potential pedagogical implications is suggested.